Development, optimization and characterization of a two step sol–gel synthesis route for ZnO/SnO2 nanocomposite - Das, Isha; Sagadevan, Suresh; Chowdhury, Zaira Zaman; Hoque, Md Enamul (Springer, 2018)
In this research, two-step sol–gel synthesis method has been used to prepare coupled semiconductor metal oxide nanocomposites of SnO2/ZnO. The structure and crystalline phase of the sample was identified using the X-ray powder diffraction analysis. The XRD pattern of SnO2/ZnO nanocomposite exhibited all the diffraction peaks for both SnO2 (tetragonal phase) and ZnO (hexagonal wurtzite phase). Surface morphological features of the prepared samples were analyzed using Scanning electronic microscopic analysis. Particle shape and size of the developed nanocomposite samples were analyzed using Transmission electronic microscopic analysis. Prepared nanoparticles have average particle size of 28 nm. EDX spectrum was used to obtain the elemental composition of the prepared sample. The peaks observed from EDX spectrum is analogous to all three elements (Sn, Zn and O) confirming the formation of SnO2/ZnO nanoparticles. Raman spectroscopic analysis was carried out to observe the peak shift of the individual composite materials. The optical properties of the samples were examined using UV–Vis reflectance and photoluminescence spectroscopic analysis. The value of band gap of SnO2/ZnO Nanocomposite was found to be 3.15 eV. The dielectric constant, dielectric loss and AC conductivity at different temperatures and frequencies were determined to obtain the typical dielectric behavior of the synthesized nanocomposite.